Clinical presentations and semen characteristics of men attending the secondary referral infertility clinic at Mumbai, India - Shagufta Afzal Khan; Vijay R Kulkarni; Rupin S Shah; Jyotsna S Gokral; Pervin K Meherji; Ashok D Vadigoppula; Anushree D Patil; Aishwarya V Bhurke; Pratibha P Kokate; Ram S Barai; Suchitra R Surve; Deepak N Modi; et al. (Wolters Kluwer Medknow Publications, 2021)
Background: Limited information is available on the aetiology and semen profiles of male infertility in Indian population. Aim: The aim of this study is to study the clinical and semen characteristics of men attending the infertility clinic and also to understand the impact of World Health Organization (WHO) 2010 reference values on the diagnosis of male infertility. Setting and Design: A retrospective study evaluating the medical case records (January 2005 to December 2015, [n = 1906]) of men attending infertility clinic in Mumbai, India. Materials and Methods: The aetiology was classified based on the andrology evaluation and other investigations. Semen profiles were compared during the years 2005-2010 and 2011-2015 using WHO 1999 and WHO 2010 criteria, respectively. Statistical Analysis: The Chi-square and Mann-Whitney U tests were performed using Open Source Epidemiological software and Social science calculators. Results: The aetiology of male infertility was determined in 62% of the men; while the cause remained undetermined in 38%. Varicocele (25%), urogenital infections (10%), sexual dysfunctions (8%) and vas aplasia (8%) were identified as major aetiologies in our cohort. Men with sexual dysfunctions and vas aplasia were significantly higher during the years 2011-2015 as compared to 2005-2010. Men having normozoospermia (10%) and azoospermia (3%) were increased, whereas those having oligoasthenozoospermia (17%) were reduced in 2011-2015 as compared to 2005-2010. According to WHO 1999 criteria , 12-15% of men showed abnormal semen profiles. The semen parameters of these men became normal on using WHO 2010 reference values. Conclusions: Varicocele is the most common aetiology in infertile men. Idiopathic infertility was seen in a higher proportion among the infertile men.